18F-florbetapir PET/MRI for quantitatively monitoring myelin loss and recovery in patients with multiple sclerosis: A longitudinal study. (July 2021) - Zhang, Min; Ni, You; Zhou, Qinming; He, Lu; Meng, Huanyu; Gao, Yining; Huang, Xinyun; Meng, Hongping; Li, Peihan; Chen, Meidi; Wang, Danni; Hu, Jingyi; et al.
Abstract: Background: Amyloid positron emission tomography (PET) can measure in-vivo demyelination in patients with multiple sclerosis (MS). However, the value of 18 F-labeled amyloid PET tracer, 18 F-florbetapir in the longitudinal study for monitoring myelin loss and recovery has not been confirmed. Methods: From March 2019 to September 2020, twenty-three patients with MS and nine healthy controls (HCs) underwent a hybrid PET/MRI at baseline and expanded disability status scale (EDSS) assessment, and eight of 23 patients further underwent follow-up PET/MRI. The distribution volume ratio (DVR) and standard uptake value ratio (SUVR) of 18 F-florbetapir in damaged white matter (DWM) and normal-appearance white matter (NAWM) were obtained from dynamic and static PET acquisition. Diffusion tensor imaging-derived parameters were also calculated. Data were expressed as mean ± standard deviation with 99% confidence interval (99%CI). Finding: The mean DVR (1.08 ± 0.12, 99%CI [1.02 1.14]) but not the mean SUVR of DWM lesions was lower than that of NAWM in patients with MS (1.25 ± 0.10, 99%CI [1.20 1.31]) and HCs (1.29 ± 0.08, 99%CI [1.23 1.36]). A trend toward lower mean fractional anisotropy (374.95 ± 45.30 vs. 419.07 ± 4.83) and higher mean radial diffusivity (0.45 ± 0.05 vs. 0.40 ± 0.01) of NAWM in patients with MS than those in HCs was found. DVR decreased in DWM lesions with higher MD (rho = -0.261, 99%CI [-0.362 -0.144]), higher AD (rho = -0.200, 99%CI [-0.318 -0.070]) and higher RD (rho = -0.198, 99%CI [-0.313 -0.075]). Patients' EDSS scores were reduced ( B = 0.04, 99%CI [-0.005 0.084]) with decreased index of global demyelination in the longitudinal study. Interpretation: Our exploratory study suggests that dynamic 18 F-florbetapir PET/MRI may be a very promising tool for quantitatively monitoring myelin loss and recovery in patients with MS. Funding: Shanghai Pujiang Program, Shanghai Municipal Key Clinical Specialty, Shanghai Shuguang Plan Project, Shanghai Health and Family Planning Commission Research Project, Clinical Research Plan of SHDC, French-Chinese program "Xu Guangqi".